Дослідження титулу на об'єкт нерухомого майна: зарубіжні реалії та вітчизняні перспективи - Спєсівцев, Д.; Spiesivtsev, D. (Волин. нац. ун-т ім. Лесі Українки, 2018)
Стаття присвячена розгляду зарубіжного досвіду, а також вітчизняних реалій та перспектив використання дослідження титулу на об’єкти нерухомого майна як інструменту визначення юридичних ризиків, пов’язаних з вчиненням правочину стосовно відповідної речі. Дослідження титулу на об'єкт нерухомого майна є ефективним інструментом визначення юридичних ризиків, пов’язаних з набуттям прав на відповідну річ, здатне спричинити позитивний вплив на цивільний оборот нерухомості, зокрема, покращити його стабільність. Ефективне функціонування досліджуваного інструменту в Україні безпосередньо залежить від наявності оперативного доступу до відповідної інформації.The article is devoted to the analysis of the foreign experience and the Ukrainian national realities and prospects of using the search of the real estate object title as a tool for determining the legal risks connected with the commission of the transaction in respect to the relevant thing. In the focus of attention are the peculiarities of the title search of the real estate object as a compulsory part of the rights transfer under the laws of France and Belgium, and its interaction with the normative provisions of ensuring the stability of civilian real estate turnover. The author provides in-depth analysis of the conditions of the effective use of the title search of the real estate object. These conditions are the rules of law since they provide legal opportunities for the relevant subjects to use the appropriate instrument for assessing legal risks, as well as the availability of necessary information resources in relation to the real estate objects. The author discusses the prospects for using the title search on a real estate object on the national market.
Title Search of the Real Estate Object: Foreign Realities and National Perspectives
Keywords: оборот нерухомості; трансфер прав; титул; ризики; державна реєстрація; real estate turnover; transfer of rights; title; risks; state registration